Acupressure, Moxibustion, and Aromatherapy for Nausea and Vomiting in First Trimester Pregnancy: A Literature Review on Potential Stunting Prevention from the Womb - Nur Maziyah Hurin'in; Nur Cholila; Tri Yunita Fitria Damayanti (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2024)
Background: Nausea and vomiting in pregnancy (NVP), often termed emesis gravidarum, is a common physiological occurrence, particularly in the first trimester, affecting 50-90% of women. While often self-limiting, severe NVP can progress to hyperemesis gravidarum, leading to dehydration, electrolyte imbalance, and malnutrition, potentially impacting maternal well-being and fetal development, thus contributing to risks associated with stunting initiated in utero. Complementary therapies offer non-pharmacological alternatives for managing NVP. Objective: This literature review aims to synthesize evidence from 22 provided journal articles on the effectiveness of acupressure, moxibustion, and aromatherapy (lemon, lavender, peppermint, ginger, orange) in managing nausea and vomiting during the first trimester of pregnancy, considering their potential role in early stunting prevention by improving maternal health. Methods: A literature search was conducted based solely on 22 Google Scholar and ScienceDirect for open-access articles published between 2020 and 2024. Keywords related to acupressure, moxibustion, aromatherapy, first-trimester nausea and vomiting, maternal weight, and maternal anxiety were used. Relevant studies meeting predefined criteria were selected and findings were synthesized narratively. Keywords related to acupressure, moxibustion, aromatherapy, first-trimester nausea and vomiting, maternal weight, and maternal anxiety were used. Relevant studies meeting predefined criteria were selected and findings were synthesized narratively. Results: The reviewed articles suggest that acupressure at Pericardium 6 (PC6) and Zusanli (ST36) is effective in reducing NVP. Moxibustion at P6 also showed positive effects, though ST36 was less effective. Aromatherapy using lemon, lavender, and peppermint essential oils consistently demonstrated effectiveness in reducing nausea and vomiting frequency and intensity. Combined aromatherapy approaches and the combination of acupressure with aromatherapy also showed benefits. Conclusion: Based on the reviewed literature, acupressure, moxibustion (particularly at P6), and aromatherapy (lemon, lavender, peppermint) appear to be effective complementary therapies for managing nausea and vomiting in the first trimester. By alleviating NVP, these non-pharmacological methods can contribute to improved maternal nutritional status and hydration, potentially supporting healthier fetal development and playing a role in strategies for stunting prevention starting from the womb.